Investigation of endophenotype potential of decreased fractional anisotropy in pediatric bipolar disorder patients and unrelated offspring of bipolar disorder patients. (28th December 2022) - Camkurt, Mehmet A.; Melicher, Tomas; Mwangi, Benson; Wu, Mon-Ju; Cao, Bo; Zeni, Cristian P.; Tannous, Jonika; Zunta-Soares, Giovana; Hasan, Khader; Sanches, Marsal; Soares, Jair C.
Abstract: Background: Bipolar disorder (BD) is a severe psychiatric disorder associated with structural and functional brain abnormalities, some of which have been found in unaffected relatives as well. In this study, we examined the potential role of decreased fractional anisotropy (FA) as a BD endophenotype, in adolescents at high risk for BD. Methods: We included 15 offspring of patients with BD, 16 pediatric BD patients, and 16 matched controls. Diffusion weighted scans were obtained on a 3T scanner using an echo-planar sequence. Scans were segmented using FreeSurfer. Results: Our results showed significantly decreased FA in six brain areas of offspring group; left superior temporal gyrus (LSTG; P  < .0001), left transverse temporal gyrus (LTTG; P  = .002), left banks of the superior temporal sulcus (LBSTS; P  = .002), left anterior cingulum (LAC; P  = .003), right temporal pole (RTP; P  = .004) and left frontal pole (LFP; P  = .017). On analysis, LSTG, LAC, and RTP demonstrated a potential to be an endophenotype when comparing all three groups. FA values in three regions, LBSTS, LTTG, and LFP were increased only in controls. Conclusion: Our findings point at decreased FA as a possible endophenotype for BD, as they were found in children of patients with BD. Most of these areas were previously found to have morphological and functional changes in adult and pediatric BD, and are thought to play important roles in affected domains of functioning. Prospective follow up studies should be performed to detect reliability of decreased FA as an endophenotype and effects of treatment on FA.